Analysis of the Role of Educational Play Activities in Early Childhood Cognitive Development - Rivaldo Rivaldo; Muhammad Luthfi Rizqi Sidiq; Andini Lestari; Satrio Adhi Pamungkas; Marisa Noviyanti Fajrah Ilsya (Universitas Negeri Semarang, 2026)
This research aims to examine how educational play activities contribute to enhancing early childhood cognitive development. The cognitive aspect is a crucial part of child development as it relates to the ability to think, solve problems, and understand their surrounding environment. This study uses a qualitative approach through a literature review supported by simple observations of children's play activities. The findings indicate that various forms of educational play, such as puzzles, building blocks, and exploratory games, can stimulate thinking abilities, improve focus, and encourage the development of children's logic and creativity. Additionally, the active role of parents and teachers in accompanying children during play also significantly influences optimal cognitive development. Thus, educational play activities can serve as an effective and enjoyable learning medium for early childhood. Therefore, proper management and utilization of play activities are necessary for children's cognitive development to reach its maximum potential.